2022
DOI: 10.1038/s41598-022-15667-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of Alzheimer’s disease-related metabolic brain pattern in biomarker confirmed Alzheimer’s dementia patients

Abstract: Metabolic brain biomarkers have been incorporated in various diagnostic guidelines of neurodegenerative diseases, recently. To improve their diagnostic accuracy a biologically and clinically homogeneous sample is needed for their identification. Alzheimer’s disease-related pattern (ADRP) has been identified previously in cohorts of clinically diagnosed patients with dementia due to Alzheimer’s disease (AD), meaning that its diagnostic accuracy might have been reduced due to common clinical misdiagnosis. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…Patients with AD fulfilled diagnostic criteria for probable AD dementia (amnestic presentation; McKhann et al, 2011 ) and had the diagnosis confirmed by cerebrospinal fluid (CSF) analysis of Aβ42 or Aβ42/Aβ40, p-tau, and t-tau according to the recent National Institute of Aging-Alzheimer’s Association research framework ( Jack et al, 2018 ). A detailed CSF procedure has been described previously ( Perovnik et al, 2022a ). Patients with DLB were diagnosed according to the 4th Consensus report of the DLB Consortium ( McKeith et al, 2017 ), followed by a diagnosis confirmation at an office visit conducted at least 12 months after the onset of symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with AD fulfilled diagnostic criteria for probable AD dementia (amnestic presentation; McKhann et al, 2011 ) and had the diagnosis confirmed by cerebrospinal fluid (CSF) analysis of Aβ42 or Aβ42/Aβ40, p-tau, and t-tau according to the recent National Institute of Aging-Alzheimer’s Association research framework ( Jack et al, 2018 ). A detailed CSF procedure has been described previously ( Perovnik et al, 2022a ). Patients with DLB were diagnosed according to the 4th Consensus report of the DLB Consortium ( McKeith et al, 2017 ), followed by a diagnosis confirmation at an office visit conducted at least 12 months after the onset of symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with FTD were diagnosed with possible FTD according to the International Behavioral Variant FTD Consortium criteria ( Rascovsky et al, 2011 ) and had their diagnosis confirmed at a follow-up visit conducted at least 12 months after the onset of symptoms. AD and DLB cohorts and their FDG PET scans included in this study have appeared previously ( Perovnik et al, 2022a , b ). NCs completed clinical, neuropsychological, and FDG PET brain imaging for purposes of an earlier research project ( Tomše et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same sliding workflow was considered with samplings of 10, 20, 30, 50, 124, and 188 patients. The choice of such different sizes was based on previous neuroscience studies that used fMRI of similar sample sizes, respectively [119][120][121][122][123][124].…”
Section: Sliding Windows and Overlapping Sliding Windowsmentioning
confidence: 99%